A longitudinal analysis of the impact of nonsurgical and surgical treatment of peri‐implantitis upon clinical parameters and implant stability quotient values. A 2-3‐year follow‐up - Peter Harrison; Edward Madeley; Michael Nolan; Stefan Renvert; Ioannis Polyzois (Wiley, 2024)
Abstract Objectives In this study, the aim was to investigate the medium‐ to long‐term impact of peri‐implantitis treatment upon clinical parameters and implant stability quotient values and to ascertain if magnetic resonance frequency analysis can be used as a diagnostic tool to demonstrate postoperative healing following treatment of peri‐implantitis. Materials and Methods A total of n = 26 patients (n = 86 implants) diagnosed with peri‐implantitis were recruited for this prospective cohort study and four different treatment modalities were used. Baseline measurements of a number of clinical parameters as well as implant stability measurements in the form of ISQ were recorded. These measurements were repeated at 6, 12, and 24-36 months following treatment. Analysis of variance was performed for all implants treated as well as separately for each treatment modality. A regression model was also used to determine factors affecting ISQ measurements over time. Results Treatment of peri‐implantitis resulted in significant improvements of both average PPDs and BOP (p < .0001 and p < .01). ISQ values marginally improved initially for all treatment modalities, but improvement was only maintained for 2-3 years in treatment modalities I (+1.28), III (+1.49), and IV (+2.92). There was a statistically significant negative linear correlation between average PPD and the ISQ values recorded both at baseline (r = −.618, p < 0.0001) and at 2/3 years (r = −.604, p < 0.0001). Conclusion Over the 2-3‐year follow‐up period, all four treatment modalities led to improved clinical and radiographic peri‐implant parameters but implant stability posttreatment, as indicated by the fact that the recorded ISQ scores remained stable. As a result, use of MRFA as an adjunct to the traditionally used periodontal and radiographic tools for the evaluation of postoperative implant stability following the treatment of peri‐implant disease cannot be recommended.